2005
DOI: 10.1021/pr0497632
|View full text |Cite
|
Sign up to set email alerts
|

Global Proteome Discovery Using an Online Three-Dimensional LC−MS/MS

Abstract: We have developed a proteomics technology featuring on-line three-dimensional liquid chromatography coupled to tandem mass spectrometry (3D LC-MS/MS). Using 3D LC-MS/MS, the yeast-soluble, urea-solubilized peripheral membrane and SDS-solubilized membrane protein samples collectively yielded 3019 unique yeast protein identifications with an average of 5.5 peptides per protein from the 6300-gene Saccharomyces Genome Database searched with SEQUEST. A single run of the urea-solubilized sample yielded 2255 unique p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 24 publications
1
84
0
Order By: Relevance
“…Three-dimensional nano LC-MS/MS proteomics analysis of nitrate-stressed biomass Total protein extracted and treated from the control and stressed samples was used for fractionation by three-dimensional liquid chromatography, followed by tandem mass spectrometry analysis to determine the protein identities, as described previously (Wei et al, 2005). The relative abundance of proteins in each sample was estimated on the basis of the hypothesis that the more abundant a peptide ion is in a mixture, the more likely it is that the peptide ion is sampled during the course of a tandem mass spectrometry experiment (Wolters et al, 2001;Liu et al, 2004).…”
Section: High-throughput Monitoring Of Cell Growth With Various Stresmentioning
confidence: 99%
“…Three-dimensional nano LC-MS/MS proteomics analysis of nitrate-stressed biomass Total protein extracted and treated from the control and stressed samples was used for fractionation by three-dimensional liquid chromatography, followed by tandem mass spectrometry analysis to determine the protein identities, as described previously (Wei et al, 2005). The relative abundance of proteins in each sample was estimated on the basis of the hypothesis that the more abundant a peptide ion is in a mixture, the more likely it is that the peptide ion is sampled during the course of a tandem mass spectrometry experiment (Wolters et al, 2001;Liu et al, 2004).…”
Section: High-throughput Monitoring Of Cell Growth With Various Stresmentioning
confidence: 99%
“…In addition to acquiring the soluble protein fraction of targeted GBM cells procured from fresh-frozen tissues, cell pellets were treated by a 1% SDS solution (Han et al 2001;Wei et al 2005) containing 20 mM Tris-HCl at pH 8.0, followed by centrifugation at 20,000 3 g for 30 min. The supernatant containing the membrane protein fraction was placed in a dialysis cup (Pierce; Rockford, IL) and dialyzed overnight at 4C against 100 mM Tris-HCl at pH 8.2.…”
Section: Tissue Microdissection and Protein Sample Preparationmentioning
confidence: 99%
“…Moreover, low abundance proteins, such as transcription factors and protein kinases, as well as hydrophobic membrane proteins, were detected. More recently, Wei et al [41] improved the MudPIT method by adding an additional reversed phase column to the biphasic column, resulting in an on-line 3D LC method. Wei et al identified 3109 yeast proteins, which is possibly the most comprehensive proteome coverage reported to date.…”
Section: Lc-based Proteomicsmentioning
confidence: 99%